The determinants of vaccination in a semi-rural area of Vientiane City, Lao People's Democratic Republic: a qualitative study - Vanphanom Sychareun; Lucy Rowlands; Phoutsomphong Vilay; Jo Durham; Alison Morgan (BMC, 2019)
Abstract Background Immunisation is a cost-effective and highly efficacious public health intervention, saving over 20 million lives in the last two decades due to decreases in childhood bacterial infections. In the Lao People's Democratic Republic, significant gaps in childhood immunisation coverage rates remain, which are a cause for concern and a barrier to the country reaching its Sustainable Development Goal targets for child health. Efforts to increase coverage have had limited success, with widening inequities being observed between urban and remote and rural areas. Methods The objectives of this study were two-fold; firstly, to describe the knowledge, attitudes and practices of mothers regarding their children's immunisation status; and, secondly, to identify individual and health system determinants of access to immunisation in five rural villages within a rural district in Lao People's Democratic Republic. This qualitative research used observation and interviews with healthcare workers (n = 10) and mothers (n = 10) with at least one child aged 12-23 months. Results The study identified several health system barriers that lower community demand for immunisation. These included the use of multiple providers, inconsistent record keeping and an inadequate health information system. At the individual and household level, there was a lack of understanding of the role of immunisation and the role of the different services provided. Conclusions The study suggests that increasing immunisation coverage in Lao People's Democratic Republic requires clearer immunisation pathways, an integrated or unified information recording system across the different levels of the health system, and strategies to increase demand, including increasing individual and household understanding of the role of immunisation in child health.